PERBEDAAN DEPRIVASI RELATIF FRATERNAL ANTARA ETNIS CINA DAN ETNIS JAWA - Noviasari, Wulan (Universitas Sahid Surakarta, 2013)
May 1998 riots was did not only caused lusted things but alive too. It was interested that in every riot that influenced by SARA (ethnic, religion, and racial issues), the Chinese found to be the victims. According to the experts, it caused by economic differences. Almost 70 percent of economic country managed by Chinese. Otherwise, as culture and population, Chinese people are only around 5 percent from all of Indonesian people. It can be affords relative fraternal deprivation at Javanese toward Chinese. Besides, Chinese role in other part of living in this country are stuck so that’s why Chinese could be in relative fraternal deprivation toward Javanese too. Relative fraternal deprivation is feeling lack of as individual (in group) when something not as well as another group (out group).